A bionic point-source polarisation sensor applied to underwater orientation. (4th September 2021) - Zhang, Teng; Yang, Jian; Guo, Lei; Hu, Pengwei; Liu, Xin; Huang, Panpan; Wang, Chenliang
Abstract: With the characteristics of full autonomy and no accumulated errors, polarisation navigation shows tremendous prospects in underwater scenarios. In this paper, inspired by the polarisation vision of aquatic organisms, a novel point-source polarisation sensor with high spectral adaptability (400 nm–760 nm) is designed for underwater orientation. To enhance the environmental applicability of the underwater polarisation sensor, a novel sensor model based on the underwater light intensity attenuation coefficient and optical coupling coefficient is established. In addition, concerned with the influence of light intensity uncertainty on sensor performance underwater, an antagonistic polarisation algorithm is adopted for the first time, to improve the accuracy of angle of polarisation and degree of polarisation in the low signal-to-noise ratio environment underwater. Finally, indoor and outdoor experiments are carried out to evaluate the performance of the designed polarisation sensor. The results show that the designed point-source polarisation sensor can acquire polarised light and be used for heading determination underwater.